2009
DOI: 10.1111/j.1365-2796.2009.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A is independently associated with metabolic risk factors but not with early atherosclerosis: the Cardiovascular Risk in Young Finns Study

Abstract: Abstract. Jylhävä J, Haarala A, Eklund C, Pertovaara

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…216 Other factors such as white blood cells and serum amyloid A have also emerged as additional downstream markers of inflammation. However, the data are not conclusive 58,108,139,219 and to date have not supplied additional predictive power above that of CRP, IL-6, and TNF-␣.…”
Section: Inflammation Beyond Crpmentioning
confidence: 97%
“…216 Other factors such as white blood cells and serum amyloid A have also emerged as additional downstream markers of inflammation. However, the data are not conclusive 58,108,139,219 and to date have not supplied additional predictive power above that of CRP, IL-6, and TNF-␣.…”
Section: Inflammation Beyond Crpmentioning
confidence: 97%
“…Like CRP, serum amyloid A (SAA) is an acute phase protein that is associated with CVD [15,18] but not with subclinical atherosclerosis [19]. Unlike CRP, SAA is mainly produced in adipose tissue under noninflammatory conditions.…”
Section: Original Articlementioning
confidence: 99%
“…Whether or not there is a relationship between age and SAA is inconsistent throughout the literature. Several studies have reported a positive correlation with age in neonates/infants with suspected infections (22) and in healthy adults (37)(38)(39), while others have shown no relationship (40,41). Since the increased SAA concentrations may be affected by numerous clinical factors that we did not adjust for (e.g., developmental variation such as premature vs. full-term infants, the presence or absence of chronic subdural hematoma or other extracranial injuries), further validation studies with increased sample size are needed to understand these potential confounders in the pediatric population.…”
Section: Articles Gao Et Almentioning
confidence: 99%